Lineshape test on overlapped transitions (R9F1, R9F2) of the 2v3 band of 12CH4 by frequency-stabilized cavity ring-down spectroscopy. (May 2018) - Yang, L.; Lin, H.; Plimmer, M.D.; Feng, X.J.; Zhang, J.T.
Highlights: The high signal-to-noise ratio spectra in the 2 v 3 band of the 12 CH4 were measured. A maximum relative fitting residual of 0.065 % was achieved. Test a series of lineshape models in the challenging case of unresolved dual-component spectra. Abstract: The performances of a multi-spectral fit for the spectra of pressure-broadened overlapping lines (R9F1, R9F2) of 12 CH4 in binary mixtures with N2 were studied by applying different lineshape models, from the simplest Voigt profile (VP) to the Harmann-Tran profile (HTP). Line-mixing was approximated in the first order in the spectral fits. Data were acquired using a high-resolution cavity ring-down spectrometer of minimum detectable absorption coefficient of 2.8 × 10 −12 cm −1 . The lines were observed with a signal-to-noise ratio of 19 365 for pressures from 5 to 40 kPa. The study reveals that the multi-spectral fits using the HTP and the speed-dependent Nelkin–Ghatak profile (SDNGP) yield the best among all tested. The two models gave the maximum relative residuals of less than 0.065 %. All things considered, the HTP and the SDNGP appear to be the most reliable models for treating the present case of multi-spectral fitting of unresolved dual-component spectra.